Expressão gênica diferencial de placas de Peyer jejunais em relação a Linfonodos mesentéricos jejunais de suínos - Machado, Juliana Gouvêa (2004)
Genes with respect to the gul defense appeared to be more expressed in the Peyer's patches (PPj) of heaíthy young pigs. In this study, the cDNA microarray technique was utilized to analyze the gene expression profile of PPj using jejunal mesenteric lymph nodes as a reference sample. Jejunal Peyer's patches and MLNj from 6 healthy young pigs among 6 and 7 weeks of age were collected. The total RNA was isolated from samples, RNA from PPj and a pool of the RNA of MLNj from each animal was used to make a microarray probe. From 2.644 genes in the microarray chip, known as the "pork chip," 33 were more expressed in PPj. Most of them are related to the cellular processes and to the celluíar metabolism; 6 are unknown genes. Ten genes were over expressed in MLNj with respect to PPj, 3 were zelated to antigen processing, and 7 are unknown genes. The microarray hybridizations were performed in duplicate with a dye-swap (Cy5 e Cy3). The microarray accuracy was proved by the real time PCR technique; aleatory genes were picked and showed coherence between the techniques. Utilizing MLNj as a reference sample, the gene expression profile of PPj was found, along with the over expression of genes related to the cellular processes and genes related to the cellular metabolism. The microarray technique was accurate for the gene expression analysis.